HERUSTIK, HERMENEUTIK SEMIOTIKA MICHAEL RIFFATERRE: (Analisis QS. Ali-Imran: 14) - Maulana, Luthfi (QOF, 2019)
Heuristic and hermeneutic is the theoretical framework of Michael Rifatere’s analysis which is used to criticize and explore the meaning of literature. In its relationship with Q.S analysis. al-Quran, it is intended to examine the meaning of the text itself, from before only interpreted at the heuristic stage and then developed analyzed using hermeneutic meaning. In the process of development, the meaning of the Koran text, especially Q.S. A<li-Imran (3): 14 will give birth to various dynamics of the meaning behind the verse until how the meaning of the verse speaks with koledor maqasid ayat. This research was felt important because in previous studies it was still rarely found which discussed the heuristic and hermeneutic analysis of Michael Riffatre to analyze the verses of the Koran, especially QS. ali-Imron: 14. Because in general previous writings only focused on the analysis of literary works such as poetry (Faruk, 1996), love poems (Mirantin, 2018) and other literary works such as poetry (Arfan, 2013), (Muchti , tt), (Syafeti, tt) and extracting meaning in various other literary works including mantra (Uniawati, 2017)